2022
DOI: 10.1186/s13063-022-06578-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing COVID Rehabilitation with Technology (ECORT): protocol for an open-label, single-site randomized controlled trial evaluating the effectiveness of electronic case management for individuals with persistent COVID-19 symptoms

Abstract: Background As of May 2022, Ontario has seen more than 1.3 million cases of COVID-19. While the majority of individuals will recover from infection within 4 weeks, a significant subset experience persistent and often debilitating symptoms, known as “post-COVID syndrome” or “Long COVID.” Those with Long COVID experience a wide array of symptoms, with variable severity, including fatigue, cognitive impairment, and shortness of breath. Further, the prevalence and duration of Long COVID is not clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 67 publications
(75 reference statements)
0
7
0
Order By: Relevance
“…In fact, according to clinical studies, rehabilitation is effective in reducing the fatigue associated with long COVID-19 [43]. It is suggested that different rehabilitation programs be developed depending on patients' needs and available resources [33]. A multidisciplinary approach to rehabilitation is suggested.…”
Section: Coordination Focused On Patient Rehabilitationmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, according to clinical studies, rehabilitation is effective in reducing the fatigue associated with long COVID-19 [43]. It is suggested that different rehabilitation programs be developed depending on patients' needs and available resources [33]. A multidisciplinary approach to rehabilitation is suggested.…”
Section: Coordination Focused On Patient Rehabilitationmentioning
confidence: 99%
“…Numerous studies also highlight the importance of adopting a care organization for long COVID patients that promotes coordination between healthcare professionals working successively in primary, secondary, and tertiary care [18,33,35]. For example, the GP is the rst point of contact for long COVID patients.…”
Section: Progressive Identi Cation Of Long Covid-19 Patient Care Path...mentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven trials are examining psychological interventions: five selfmanagement programs (Blázquez, 2022;Busse & Potter, 2022;Chantal, Hiyam, & Karen, 2021;Collette, Willems, Cabello, & Lesoinne, 2022;Culos-Reed & Twomey, 2021;Martin & Lynall, 2022), three cognitive-behavioral therapy interventions (Acartürk & Öztürk, 2021;Håkansson, Hartman, & Cronhjort, 2021;Martin & Lynall, 2022) (one with components of acceptance and commitment therapy and one using peer support), two meditation interventions (Croghan, Hurt, Fokken, & Currie, 2022;Subramaniam, 2021), one psychoeducational intervention (Collette et al, 2022), and one case-management intervention (Hatcher, Ward, & Edgar, 2021). Components of multidisciplinary care are present in several; for example, a cognitive-behavioral therapy intervention includes stretching exercises (Acartürk & Öztürk, 2021), while other interventions include psychoeducation across cognition, diet, breathing, and other spheres of life (Blázquez, 2022;Busse & Potter, 2022;Culos-Reed & Twomey, 2021;Martin & Lynall, 2022).…”
Section: Psychological Interventionsmentioning
confidence: 99%
“…clinical distress or a positive screen for clinical depression or anxiety (Acartürk & Öztürk, 2021;Håkansson et al, 2021), another includes cognitive impairment as an inclusion criterion (Collette et al, 2022), and one lists quality-of-life impairments as a requirement to participate (Hatcher et al, 2021). Six trials exclude individuals with severe or acute mental illness, or a history of mental illness (Acartürk & Öztürk, 2021;Blázquez, 2022;Collette et al, 2022;Croghan et al, 2022;Håkansson et al, 2021;Subramaniam, 2021), and two exclude individuals with substance use disorders (Acartürk & Öztürk, 2021;Collette et al, 2022); severe cognitive deficits are an exclusion criterion for three trials (Collette et al, 2022;Hatcher et al, 2021;Håkansson et al, 2021). (Melamed, Collins, & Palm, 2021), and atorvastatin (Anderson & Carcel, 2021).…”
Section: Psychological Interventionsmentioning
confidence: 99%